PENERAPAN PENDIDIKAN SEKSUAL OLEH GURU DAN ORANG TUA BAGI REMAJA BERKEBUTUHAN KHUSUS - Niken Widi Astuti; noeratri andanwerti (Fakultas Psikologi Universitas Tarumanagara, 2017)
Sex education for adolescent with special needs becomes a necessity. In term of it, besides based on philosophical a juridical, sex education is the preventive efforts in order that every child with special needs can recognize, understand in handle biological development and change. In addition sex education for adolescent with special needs also aims at guiding them to appreciate others people’s sexual behavior and not to make them being stuck on deviate sex conduct as well as not getting violence and sexual abuse from others. This is because their physical and psychological condition, which has some problems, enables them to be easily manipulated and courted so that many of them are often stuck to be an object of sexual harassment of irresponsible person. The method used is qualitative method in form of case study, data collection, using interviews and observation. Subjects in this research were two teachers and three parents. This research specifically is going to explain the concept of sexual education for adolescent with special needs, the anvil of sex education, as well as material, method, parents and teacher competencies in the implementation of sex education for them. Keywords: sex education, the adolescent with special needs